FOREIGN OWNERSHIP AND FIRM VALUE: THE MODERATING ROLE OF TAX AVOIDANCE IN INDONESIAN LISTED FIRMS - Krisyadi, Robby; Pangrani, Zoey; Chandra, Budi (Assets : Jurnal Ekonomi, Manajemen dan Akuntansi, 2025)
This study analyzes the effect of foreign ownership on firm value and evaluates whether tax avoidance moderates this relationship. The study uses panel data of companies listed on the Indonesia Stock Exchange during the period 2019–2023. The sample was selected using purposive sampling, resulting in 1,940 observations. Model estimation was performed using panel regression processed through STATA software, taking into account company size, leverage, asset growth, company age, and market capitalization as control variables. The results show that foreign ownership has a positive effect on firm value, and this effect is stronger in companies with higher effective tax rates, reflecting lower levels of tax avoidance. These findings indicate that foreign investors place a higher value on companies that not only have a large proportion of foreign ownership but also demonstrate stronger fiscal compliance and transparency. This study contributes by showing that the benefits of foreign ownership are greatly influenced by corporate tax behavior, thereby helping to explain the inconsistency of empirical findings in previous studies.